Modernism and the women's popular romance in Britain, 1885-1925 - Hipsky, Martin (Ohio University Press, 2011)
Today's mass-market romances have their precursors in late Victorian popular novels written by and for women. In Modernism and the Women's Popular Romance Martin Hipsky scrutinizes some of the best-selling British fiction from the period 1885 to 1925, the era when romances, especially those by British women, were sold and read more widely than ever before or since. Recent scholarship has explored the desires and anxieties addressed by both "low modern" and "high modernist" British culture in the decades straddling the turn of the twentieth century. In keeping with these new studies, Hipsky